Rapid frontotemporal gray matter loss in proposed body-first Parkinson’s disease: a longitudinal voxel-based morphometry study - Jin Yan; Ge Yao (Frontiers in Neurology, 2025)
ObjectiveThe study aimed to compare the progressive gray matter (GM) atrophy between brain-first and body-first Parkinson’s disease (PD) under assumption.MethodsBased on the hypothesis that the timing of rapid eye movement (REM) sleep behavior disorder (RBD) onset relative to motor symptoms may differentiate brain-first from body-first PD subtypes, we stratified PD patients from the Parkinson’s Progression Markers Initiative (PPMI) database into 28 RBD-positive PD patients (PDRBD+), 26 RBD-negative PD patients (PDRBD-), 33 isolated RBD (iRBD) patients, and 35 healthy controls. PDRBD+ and PDRBD− groups underwent 4 visits within 48 months including clinical assessments and structure MRI. We measured GM atrophy cross-sectionally and longitudinally and analyzed their associations with other proposed markers.ResultsAt baseline, all groups were comparable and showed no significant difference in GM volume (GMV). The longitudinal GMV analysis (group-by-time interaction) showed that, compared with PDRBD− group, PDRBD+ demonstrated significant GM loss in the medial surface of the frontal lobes and the left temporal lobe. In the comparison at the 48th month, besides the bilateral frontotemporal lobes, the PDRBD+ group showed significant GM atrophy in the bilateral cerebellum. The two groups had no significant differences in the 12th and 24th months. Over time, each PD group showed extensive cortical GM loss and bilateral caudate and putamen atrophy. The altered GMV (interaction effect) was positively associated with the MoCA scores and negatively with SCOPA-AUT. Furthermore, the group-level F-statistic map highlighted spatially distinct differences in the protein metabolism, signal transduction, and autophagy pathways between PDRBD+ and PDRBD− groups.ConclusionBody-first PD patients show a relatively rapid GMV loss in specific frontotemporal regions (e.g., left middle temporal gyrus) within 6 years following motor symptoms. Our findings add further evidence to the α-synuclein spreading hypothesis.